Efektivitas Media Pembelajaran Powtoon Berbantukan Game Based Learning Terhadap Kemampuan Berhitung Perkalian di SDN Lombang, Sumenep - Nisa, Khoirun; Meita, Nisfil Maghfiroh; Andiriyanto, Ach. (Jurnal Studi Multidisiplin Qomaruna, 2025)
Multiplication numeracy skills are a fundamental competency in elementary mathematics education; however, in practice, many students still experience difficulties due to the use of learning media that are limited in variety and predominantly conventional. The utilization of technology-based learning media combined with active learning approaches, such as Game-Based Learning (GBL), is considered to have the potential to enhance student engagement and understanding. This study aims to examine the effectiveness of Powtoon-based learning media supported by GBL on the numeracy skills of third-grade students at SDN Lombang, Sumenep. The population of this study consisted of 32 third-grade students. A quantitative approach was employed using a quasi-experimental design. The research sample comprised 15 students in the experimental group and 17 students in the control group. Data were collected through tests, observations, and interviews. The results of the analysis indicated that the mean score of the experimental group (80.90) was higher than that of the control group (68.88). Hypothesis testing using an Independent Samples t-test showed a significant t-value of 7.550 (p<0,05). Accordingly, Powtoon-based learning media supported by Game-Based Learning were found to be effective in improving the multiplication numeracy skills of third-grade students.